Efek Pemberian Paket Kasih terhadap Keberlanjutan Bounding Attachment pada Ibu Post Sectio Caesarea - Westy Tahapary; Irna Nursanti; Giri Widagdo (Journal of Telenursing (JOTING), 2022)
This study aims to determine the effect of giving a love package on the sustainability of bounding attachments in post Sectio Caesarea (SC) mothers. The method used is quasi-experiment with pre and post-test without control. Data analysis was performed using the Wilcoxon test. The results showed a significant difference between role achievement, maternal identity and closeness to the continuity of post-SC maternal bounding attachment (p = 0.000). In conclusion, the love package affects the sustainability of the bounding attachment. The love package can also be used as a nursing intervention in post-SC maternal support programs in hospitals or other health facilities. Keywords: Bounding Attachment, Mother Post Sectio Caesarea, Love Package